The IAA to the Rescue (The Biblical archaeology review, 2022)
Gideon Avni, who heads the Archaeological Division of the Israel Antiquities Authority (IAA), began his archaeology career in 1980. Since then, he has conducted extensive archaeological fieldwork throughout Israel. Here, Avni discusses the topic of salvage excavation. To read the full interview with BAR, visit biblicalarchaeology.org/rescue. (1) 2 3 4 5 What is a […]